ANALYSIS OF PUBLIC OPINION SENTIMENT REGARDING POLICE INSTITUTIONS BASED ON TWITTER USING THE SUPPORT VECTOR MACHINE (SVM) METHOD - Sirojudin, Said Ahmad; Susanti, Try; Aribangsa, Mhd Theo (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2024)
Abstract: Twitter occupies the top position of the most popular social media platform in Indonesia. Police and other related issues were the subject of much discussion. The aim of this research is to analyze public sentiment towards the National Police Agency using Twitter with the support vector machine method. The research started by crawling Twitter data. The data contains a total of 6,925 entries for three keywords. Next, we move on to the preprocessing stage consisting of (cleaning, case folding, tokenization, and filtering). Next is the tf-idf feature extraction stage, finally the classification and evaluation stage. The results of manual data inspection (73:27) showed accuracy of 70.66%, precision of 70.68%, and recall of 99.76%. Testing the second data (82:18), found accuracy 86%, precision 86.21%, recall 99.71%. The results of manual data checking (82:18) showed accuracy of 70.66%, precision of 70.68%, recall of 99.76%. Testing the second data (82:18), found accuracy 86%, precision 86.21%, recall 99.71%. From the data system testing results (80:20), accuracy was 87.55%, positive precision 87.53%, negative precision 88.24%, positive recall 99.48%, and negative recall. the rate is 99.48.% – The result is 21.43%. Data testing results (60:40) showed accuracy of 86.89%, positive precision of 86.84%, negative precision of 88.46%, positive recall of 99.61%, and negative recall of 16.43%. Single test data validation system (80:20), accuracy 87.55, overall test cross validation system (k fold 5 accuracy) 86.673%. Keywords: data mining;police agencies;support vector machines Abstrak: Twitter menduduki posisi teratas platform media sosial terpopuler di Indonesia. Polisi dan masalah terkait lainnya menjadi pokok bahasan banyak pembicaraan. Tujuan penelitian ini untuk menganalisis sentimen masyarakat terhadap Badan Kepolisian Nasional menggunakan Twitter dengan  metode support vector machine. Penelitian dimulai dengan  crawling  data Twitter. Data memuat total 6.925 entri dari tiga kata kunci. Selanjutnya beralih ke tahap preprocessing terdiri dari (pembersihan, pelipatan kasus, tokenisasi, dan pemfilteran). Selanjutnya tahap ekstraksi fitur tf-idf, terakhir tahap klasifikasi dan evaluasi. Hasil pemeriksaan data manual (73:27) menunjukkan akurasi 70,66%, presisi 70,68%, dan recall 99,76%. Menguji data kedua (82:18), menemukan akurasi 86%, presisi 86,21%, recall 99,71%. Hasil pemeriksaan data secara manual (82:18) menunjukkan akurasi 70,66%, presisi 70,68%, recall 99,76%. Menguji data kedua (82:18), menemukan akurasi 86%, presisi 86,21%, recall 99,71%. Dari hasil pengujian sistem data (80:20), akurasi 87,55%, presisi positif 87,53%, presisi negatif 88,24%, recall positif 99,48%, dan recall negatif. tarifnya adalah 99,48.% – Hasilnya 21,43%. Hasil pengujian data (60:40) menunjukkan akurasi 86,89%, presisi positif 86,84%, presisi negatif 88,46%, recall positif 99,61%, dan recall negatif 16,43%. Uji tunggal sistem validasi data (80:20), akurasi 87,55, uji keseluruhan sistem validasi silang  (akurasi k fold 5) 86,673%. Kata Kunci: data mining;instansi kepolisian;mesin vektor pendukung